2019
DOI: 10.1080/0886022x.2019.1578234
|View full text |Cite
|
Sign up to set email alerts
|

Kidney injury molecule-1 expression predicts structural damage and outcome in histological acute tubular injury

Abstract: Background: A few studies have shown that urinary kidney injury molecule-1 (uKIM-1) levels are increased in acute kidney injury (AKI); however, the correlation between uKIM-1 and histological tubular injury, which is considered to be the gold standard for evaluating renal damage and predicting prognosis, is still unclear. We performed this study to determine whether the predicted value of uKIM-1 is correlated with renal KIM-1 (tKIM-1) expression and tissue damage in AKI patients. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 23 publications
2
18
0
6
Order By: Relevance
“…6). The Kim-1 ROC AUC of 1.0 in this study is comparable to other findings (26, 39), whereas glycosuria shows an AUC of 0.93, showing that both markers have high sensitivity and specificity for colistin-induced AKI. The interesting finding that urinary Kim-1 levels did not correlate with urinary glucose in samples collected after 7 days of colistin treatment suggests that both markers can offer separate and equally relevant information on early renal injury.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…6). The Kim-1 ROC AUC of 1.0 in this study is comparable to other findings (26, 39), whereas glycosuria shows an AUC of 0.93, showing that both markers have high sensitivity and specificity for colistin-induced AKI. The interesting finding that urinary Kim-1 levels did not correlate with urinary glucose in samples collected after 7 days of colistin treatment suggests that both markers can offer separate and equally relevant information on early renal injury.…”
Section: Discussionsupporting
confidence: 88%
“…Urinary Kim-1 levels have been assessed under colistin treatment in rats, with the report that it is a specific marker of proximal tubular damage (22), with very low expression in healthy kidney tissue (23, 24). Histology is the ideal gold standard for assessing tubular injury, although not always feasible, with Kim-1 representing an example where histological examination and urinary output of the marker have been shown to correlate closely both in rodents and humans (25, 26).…”
Section: Introductionmentioning
confidence: 99%
“…Kidney fibrosis, a condition that causes impaired renal function, was increased in the DR+NF group but not in the HFD group. In an earlier literature review, uKIM-1 level correlated with the severity of renal histological damage, and can be a potential reliable predictor of adverse renal outcomes in acute tubular injury [ 25 ], and KIM-1 is a sensitive tissue indicator of AKI [ 26 ]. TNF-α, which causes inflammatory cell injury, can significantly induce the expression of the apo-A4 protein, which is also associated with pro-inflammatory acute kidney injury in human kidney cells [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In their another study, Belcher et al observed that multiple structural biomarkers of kidney injury were independently associated with progression of AKI and mortality in patients with cirrhosis, but their levels were similar to those without progression and those with progression alone [3]. Finally, Cai et al performed an observation that aimed to determine whether the predicted value of urine KIM-1 is correlated with renal KIM-1 expression and tissue damage in AKI patients [28]. The authors observed a close relationship between the severity of renal histological damage and the urine KIM-1 level.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Cai et al. performed an observation that aimed to determine whether the predicted value of urine KIM-1 is correlated with renal KIM-1 expression and tissue damage in AKI patients [ 28 ]. The authors observed a close relationship between the severity of renal histological damage and the urine KIM-1 level.…”
Section: Discussionmentioning
confidence: 99%